Pathophysiology and clinical management of coronavirus disease (COVID-19): a mini-review - Zhu, Ying; Sharma, Lokesh; Chang, De (Frontiers in Immunology, 2023)
An unprecedented global pandemic caused by a novel coronavirus named SARS-CoV-2 has created a severe healthcare threat and become one of the biggest challenges to human health and the global economy. As of July 2023, over 767 million confirmed cases of COVID-19 have been diagnosed, including more than 6.95 million deaths. The S protein of this novel coronavirus binds to the ACE2 receptor to enter the host cells with the help of another transmembrane protease TMPRSS2. Infected subjects that can mount an appropriate host immune response can quickly inhibit the spread of infection into the lower respiratory system and the disease may remain asymptomatic or a mild infection. The inability to mount a strong initial response can allow the virus to replicate unchecked and manifest as severe acute pneumonia or prolonged disease that may manifest as systemic disease manifested as viremia, excessive inflammation, multiple organ failure, and secondary bacterial infection among others, leading to delayed recovery, hospitalization, and even life-threatening consequences. The clinical management should be targeted to specific pathogenic mechanisms present at the specific phase of the disease. Here we summarize distinct phases of COVID-19 pathogenesis and appropriate therapeutic paradigms associated with the specific phase of COVID-19.